False symptoms, genuine suffering: Munchausen Syndrome as a challenge for contemporary medicine - Biecka, Adrianna; Wyrzykowski, Mikołaj; Szczepanek, Dawid; Szczurek, Katarzyna (Quality in Sport, 2025)
Background: Munchausen Syndrome, classified as a factitious disorder, is a psychiatric condition in which individuals deliberately fabricate or induce medical symptoms to assume the role of a patient. Despite its rarity, the disorder poses significant diagnostic and therapeutic challenges due to its deceptive nature and frequent comorbid psychiatric conditions. Misdiagnosis can lead to unnecessary medical procedures, increased healthcare costs, and delayed psychiatric intervention. This review aims to provide a comprehensive overview of the syndrome, emphasizing its epidemiology, clinical presentation, and treatment approaches. Materials and Methods: A systematic review was conducted using PubMed and Google Scholar databases. Keywords such as "Munchausen Syndrome," "factitious disorder," and "psychiatric deception" were used to identify relevant publications. Twenty four articles were selected based on their relevance to the disorder’s epidemiology, clinical manifestations, and treatment. Case reports, retrospective studies, and systematic reviews were analyzed to synthesize current knowledge on the syndrome. Conclusions: Munchausen Syndrome remains a complex and underdiagnosed disorder that requires increased awareness among medical professionals. Diagnosis relies on identifying behavioral patterns and ruling out genuine medical conditions, while treatment focuses on psychotherapeutic intervention, like cognitive-behavioral therapy (CBT). Although pharmacotherapy does not directly address the syndrome, it may be beneficial in managing co-occurring psychiatric conditions. A multidisciplinary approach, including structured medical oversight and improved communication between healthcare providers, is crucial for improving patient outcomes and preventing unnecessary medical interventions.